(untitled) (Asian Journal of Pharmaceutics (AJP), 2019)
Background and Objective: The most important tool which helps bacteria to tolerate survival in unwanted conditions and resistance to new generations of antimicrobial agents is biofilm formation through quorum sensing. This study aimed to detect biofilm formation using study isolates of staphylococci quantitatively. Further, concerning minimal inhibitory concentration (MICs), biofilm inhibitory concentration (BICs), and minimum biofilm eradication concentrations (MBECs), to determine biofilm antimicrobial susceptibility test for selected antimicrobial agents against the study isolates. Patients and Methods: A total of 28 catheter urine specimens and wound swabs belonged to 32 patients admitted to Ramadi Teaching Hospital during the period from February to June 2009 were included in this study. Quantitative assay by a spectrophotometric method with ELISA reader was achieved. Planktonic and biofilm antimicrobial susceptibility tests for planktonic and sessile cells performed. Results: Out of 12 (37.5%) isolates of Staphylococcus epidermidis and 20 (62.5%) isolates of Staphylococcus aureus, biofilms were produced in 100% of all study isolates and produced biofilm actively in the glucose supplemented media. Our result revealed that MICs were 2.1 ± 1.2 μg/ml, 46.7 ± 18.6 μg/ml, and 3.25 ± 1.86 μg/ml for ciprofloxacin, piperacillin, and amikacin, respectively, against logarithmic phase planktonic cells of Staphylococcus spp. Furthermore, BICs and MBECs for the selected antimicrobial agents were reached ×50–100 folds higher than MICs to inhibit and eradicate staphylococcal biofilm. Conclusion: All study isolates of staphylococci produced biofilm quantitatively in glucose supplemented media. Furthermore, in biofilm antimicrobial susceptibility test, the biofilm producing isolate isolates of staphylococci required ×50–100 fold higher than those values for MICs for the same strains with the planktonic state to inhibit and remove bacterial biofilm from the surface of catheters.